High-Throughput Illumina MiSeq Amplicon Sequencing of Yeast Communities Associated With Indigenous Dairy Products From Republics of Benin and Niger - Sessou, Philippe; Keisam, Santosh; Tuikhar, Ngangyola; Gagara, Mariama; Farougou, Souaïbou; Jeyaram, Kumaraswamy (Frontiers in Microbiology, 2019)
Traditional cheese Wagashi and fermented cow milk are among the most popular dairy products appreciated by people from Benin, Niger and neighboring region. These products are the main source of protein in the diet of low-income population in the region. The fermented milk is prepared by spontaneous fermentation without back-slopping. Whereas, the leaf extract of Calotropis procerea is used for curdling the milk to prepare the soft cheese Wagashi. The present study aims to provide in-depth analysis of yeast communities associated with these traditional milk products by high-throughput Illumina MiSeq amplicon sequencing of internal transcribed spacer (ITS) region of fungal rRNA genes. A total of sixty samples, twenty samples of fermented milk each from Benin and Niger, and twenty samples of cheese Wagashi from Benin were used for analysis. Metagenomic investigation revealed that Kluyveromyces marxianus, Saccharomyces cerevisiae, Candida parapsilosis, and Sagenomella keratitidis were the predominant yeast species present in the traditional milk products. Furthermore, we noticed a high presence of K. marxianus (61.1 % relative abundance) in the cheese Wagashi and S. cerevisiae (28.4 % relative abundance) in the fermented milk of Niger. The presence of potential pathogenic yeast C. parapsilosis, and S. keratitidis in these African milk products, calls for further investigation to assess their safety. The predominant yeast K. marxianus and S. cerevisiae, recognized with generally regarded as safe (GRAS) status could be further selected as starter culture along with lactic acid bacteria for developing controlled fermentation processes with enhanced product quality and safety.